The Effect of Self-Regulation Empowerment Program Training on Neurocognitive Functions of Students with Mathematics Disorder - Ebrahim Rahbar Karbasdehi; Abbas Abolghasemi; Abbasali Hossein Khanzadeh (Iranian Association of Health Education and Health Promotion, 2018)
Background and Objective: Students with mathematics disorder are faced with various neurocognitive factors, that affect their quality of life. Considering the relationship between neurocognitive functions with self-regulation, one of the methods capable of assisting the students with mathematics disorder is the self-regulation empowerment training. The current study aimed at determining the effect of self-regulation empowerment program training on neurocognitive functions in students with mathematics disorder.  Methods: The study was a semi-experimental with pretest/posttest design and a control group. The study sample was consisted of 26 students with mathematics disorder in Rasht city in 2018, selected by the convenience sampling method and randomly assigned into two equal groups. To collect the data, tower of Hanoi task, stroop test, dual n-back task, and Wisconsin card sorting test were used before and after the intervention. A twelve-session self-regulation empowerment program training was implemented for the experimental group. Data was analyzed using multivariate analysis of covariance by SPSS 24. Results: The results showed that there was a significant difference in the mean scores of experimental and control groups in all four neurocognitive functions. In other words, self-regulation empowerment program training leads to promote the executive planning, selective attention, working memory performance and cognitive flexibility of students with mathematics disorder (P< 0.001). Conclusion: According to the findings of the research, self-regulation empowerment training can improve the neurocognitive functions in students with mathematics disorder. Therefore, it is suggested that this intervention applies for training students with mathematics disorder.